2020
DOI: 10.18178/ijiet.2020.10.12.1477
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Engagement in Rotational Motion via Flipped Classroom and 5E Instructional Model

Abstract: This study determined the effectiveness of using a flipped classroom approach and the 5E instructional model in teaching the Physics topic, Rotational Motion. Using mixed methods, this study involved ten Grade 12 students under the Science, Technology, Engineering, and Math (STEM) track. Data showed that the implementation of the four-week study was successful. The students developed a sense of responsibility, participated in the discussion, and followed instructions as a result of the highly positive and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…The study reported positive coreelation between students' performance and the application of the 5E model. A study conducted by (Rafon & Mistades, 2020) aimed to evaluate the implementation of the 5E Instructional Model in teaching the physics topic to Science, Technology, Engineering, and Mathematics (STEM)…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The study reported positive coreelation between students' performance and the application of the 5E model. A study conducted by (Rafon & Mistades, 2020) aimed to evaluate the implementation of the 5E Instructional Model in teaching the physics topic to Science, Technology, Engineering, and Mathematics (STEM)…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the former literature, several studies were found on both the 5E learning cycle and academic achievement and attitude towards various fields of science (DEMİR & İrfan, 2020; Lu et al, 2020;Ohn-Sabatello, 2020;Ong et al, 2018;Rafon & Mistades, 2020). However, few studies were dedicated to investigating the effects of the 5E learning cycle on learning the social sciences and humanities subjects (Suwito et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Through the 5E instructional model, it is hoped that students will become active in constructing previous knowledge and connecting with new knowledge so that learning objectives are achieved and also make students become independent and work together to find concepts (Rafon & Mistades, 2020). .…”
Section: Developmentmentioning
confidence: 99%
“…From their initiative, finally, all of their students, whether they can attend the class or not, were required to access the learning video at home to review and reinforce classroom lessons (Tucker, 2012). In a traditional classroom, students spend time listening for the explanation of the learning content from the teacher, but with FC, the video of learning materials was provided before class and students need to watch at home, while the classroom contact hours are filled with interactive and collaborative learning opportunities (Rafon & Mistades, 2020). FC environment allows the students to be involved directly in active learning, and because of that, FC contributes a positive impact on student learning outcomes and attitudes toward the learning process (Olakanmi, 2017).…”
Section: Defining the Flipped Classroom Approachmentioning
confidence: 99%